The Role of Socio-Economic and Technological Dimensions in Improving Environmental Quality - Meita Indah Fadilla; Nurhayati Nurhayati; Erista Nurfiningrum (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2024)
Environmental quality is one of the cornerstones in realizing sustainable development. The shift in economic sectors that Indonesia has experienced has resulted in environmental degradation that poses a severe threat to the quality of life of people and biodiversity, affecting economic sustainability. The economic transformation that is carried out changes human activities to affect the happiness and ease of access that people get and the existence of technology transfer activities. In addition, changes in the economic sector can increase regional income due to increased productivity. This increase in income can cause inequality between communities that can affect environmental quality. This study aims to analyze environmental determinants, including socioeconomic dimensions and technology use in the community. The method used is quantitative with multiple linear regression analysis through the Ordinary Least Square (OLS) technique. The data used is secondary data that is a cross-section of 34 Indonesian provinces in 2021 because it adjusts to the availability of data. The results showed that happiness and the use of technology have a positive but insignificant influence on environmental quality. In addition, income inequality, Human Development Index, and Gross Regional Domestic Product negatively influence on environmental quality.Keywords: Socio-economic, technological dimension, environmental quality.